Iraq : Staff-Monitored Program-Press Release; and Staff Report. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses the Iraqi authorities' request for a Staff-Monitored Program (SMP). The authorities have requested an SMP to establish a track record of policy credibility to pave the way to a possible IMF financing arrangement. Under the SMP, the authorities will implement fiscal consolidation that will contain public expenditure in line with available revenue and financing, and aim to reduce the non-oil primary deficit by USD 20 billion or 12 percent of non-oil GDP between 2013 and 2016. Under the SMP, agreement has also been reached on measures to strengthen public financial management, anti-money laundering and countering the financing of terrorism, and financial sector stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet